2016
DOI: 10.3892/or.2016.4919
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endoplasmic reticulum stress and p53 in lncRNA MEG3-induced human hepatoma HepG2 cell apoptosis

Abstract: Long non-coding RNAs (lncRNAs) play important roles in diverse biological processes. Although downregulation of lncRNA maternally expressed gene 3 (MEG3) has been identified in several types of cancers, little is known concerning its biological role and regulatory mechanism in hepatoma. Our previous studies demonstrated that MEG3 induces apoptosis in a p53-dependent manner. The aim of the present study was to determine whether endoplasmic reticulum (ER) stress is involved in MEG3‑induced apoptosis. Recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 33 publications
8
35
0
Order By: Relevance
“…Previous studies have suggested that MEG3 increased the p53 activity in cancer cells [24, 25]. Because pulmonary hypertension and cancers have similar pathological processes, like cell proliferation increased and apoptosis decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that MEG3 increased the p53 activity in cancer cells [24, 25]. Because pulmonary hypertension and cancers have similar pathological processes, like cell proliferation increased and apoptosis decreased.…”
Section: Resultsmentioning
confidence: 99%
“…As lncRNAs may be pivotal in many biochemical pathways20, we explored whether cancer risk lncRNAs from different cancer datasets display a similar regulation pattern with their cancer risk pathways or not. A total of 23 lncRNAs which involved in the regulation of cancer risk pathways were identified as cancer risk lncRNAs in the six cancer datasets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some studies have shown that lncRNAs influence the UPR. Overexpression of lncRNA MEG3 has been documented to induce ER stress markers (eg, IRE1α) and also induces apoptosis in human hepatoma cells, 23 whereas gain of function of lncRNA TUG1 partly blocked ER stress pathways and was organ protective in a model of cold-induced liver injury in mice. 24 ER stress affects multiple cellular processes and may result in adaptive or proapoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…16 To date, only few lncRNAs have been shown to be associated with the unfolded protein response (UPR). [22][23][24] Kato et al 22 recently demonstrated that lnc-MGC, which is induced by ER stress, is upregulated in a mouse model of diabetic nephropathy. In addition, some studies have shown that lncRNAs influence the UPR.…”
Section: Discussionmentioning
confidence: 99%